Expressive Speech Acts in the Kpu.Ri Instagram Comments - Ulfa Nafila; Rika Ningsih (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research delves into the multitude of expressive speech acts evident in the Instagram comment section of the KPU Statement concerning the 2024 Presidential and Vice Presidential Candidate Debate during the 2024 Election, particularly on the official KPU_RI Instagram account. It aims to address the prevalence and nature of these speech acts within the @KPU_RI Instagram comments. Employing a qualitative approach with content analysis methods, this study explores and elaborates on expressive speech acts in response to the KPU_RI Instagram post titled "KPU's Statement Regarding the 2024 Election Debate and Vice Presidential Candidates". Data collection involves extracting comments from KPU statement uploads on the KPU_RI Instagram account containing expressive speech acts, utilizing documentation, listening, and note-taking techniques. Analysis entails coding, data classification to identify relationships, and drawing conclusions. The findings reveal 199 instances of expressive speech acts, including praise, congratulations, criticism, gratitude, blame, and condolences. Notably, criticism emerges as the dominant form, reflecting public dissatisfaction or disagreement with KPU's decisions or policies regarding the 2024 Presidential and Vice-Presidential Election debate. These insights shed light on the dynamics of expressive speech acts in online discourse surrounding electoral processes.